Synthesis and Crystal Structure of New Nickel(II) Complex with Salen-Type Bisoxime Ligand - Sun*, Yin-Xia; Zhang, Yu-Jie; Meng, Wei-Sheng; Li, Xin-Ran; Lu, Rui-E (Asian Journal of Chemistry, 2014)
A new nickel(II) complex, [(NiLMeOH)2(OAc)2Ni]·2MeOH, has been synthesized via the complexation of nickel(II) acetate tetrahydrate with a new Salen-type bisoxime ligand (H2L). X-Ray crystal structure determination of the nickel(II) complex shows that the hexa-coordinated terminal nickel(II) atoms lie in the N2O2 coordination sphere of Salen-type bisoxime ligands, quadruple μ-phenoxo oxygen atoms from two [NiL] chelates coordinated to the central nickel(II) atom and the two acetate anions coordinated to three nickel(II) atoms through Ni-O-C-O-Ni bridges. Thus, all the three nickel(II) atoms of the Ni(II) complex have distorted octahedral geometries.